Fatigue and TSH Levels in Hypothyroid Patients - El-Haddad, Boutros; El Bizri, Issam; Kallail, K James; Zackula, Rosalee E; Hoffman, Jan M (Kansas Journal of Medicine, 2012)
Background. Fatigue is often the complaint that initiates thyroid function investigation. Most available data related to fatigue and hypothyroidism involved patients with subclinical hypothyroidism where fatigue was not the primary outcome. This study investigated the association between TSH levels and fatigue and if there was a target TSH interval that was associated with lower incidence of fatigue in patients with hypothyroidism. Methods. An analytic, retrospective cohort study design assessed the relationship between TSH levels and fatigue. All adult patients at one endocrinology clinic who were diagnosed with hypothyroidism between January 1, 2006 and December 31, 2007 were included. Diagnoses were confirmed by biochemical testing. Data were abstracted from the clinic’s electronic medical record. Fatigue status was self-reported by the subject during examination by the endocrinologist. Fatigue status and TSH levels were obtained twice: at diagnosis and during the first follow-up visit. Results. A total of 135 patients met the inclusion criteria. After treatment, all patients had reductions in TSH levels. Those subjects reporting relief from fatigue tended to be males (p = 0.003), had lower TSH levels at follow-up (p < 0.001), had larger TSH differences from baseline (p =0.007), and had a primary diagnosis of acquired hypothyroidism (p < 0.001). Females were 2.9 times more likely to report persistent fatigue than males. Patients with primary diagnosis of thyroiditis were 3 times more likely to report persistent fatigue than those with acquired hypothyroidism. Conclusions. The observed relief from fatigue after treatment correlated with a higher TSH reduction compared to patients with persistent fatigue. It was unclear if fatigue relief was related to the level of TSH reduction (TSH difference) or to a lower absolute TSH level reached after treatment.